O projeto Roteiro Geo-Turístico em Porto Nacional- TO: um instrumento de educação patrimonial - Ribeiro, Laíres José Gonçalves da Silva (Universidade Federal do Tocantins, 2022)
Heritage education through cultural tourism has shown itself to be a possibility of transforming teaching experience, providing students with diverse sociocultural and environmental knowledge, in addition to contributing to the improvement and development of citizenship. Therefore, this work aims to make a brief approach on heritage education and cultural tourism in order to understand their meanings and contexts, aiming to understand the contribution of the Geo- Tourism Route Project of Porto Nacional, as a tourist and educational activity, seeking promote and demonstrate it through pedagogical practice. Places are understood as important and meaningful spaces, which are developed by those who reside or visit. Geography and tourism, two areas of study, intertwine as possible interpretations to reproduce the imaginary of reality, building and giving meaning. The methodological procedures were subsidized through qualitative analysis, literature review, document analysis, questionnaire and the methodology of Salete Kozel, which aims to interpret/decode what can be transmitted through representations made by the subjects, seeking to understand what is impregnated in the imagination of those who live experiences in a particular place. Thus, through mental maps prepared by five (ex) monitors who experienced the Historic Center of the city of Porto Nacional-TO acting in tour classes, it was possible to understand the different perceptions of this urban-tourist space of the Geo- Tourism Route Project of National Port. The investigation found that heritage education activities contribute to the development of cultural tourism and boost the conservation and preservation of cultural assets when they appropriate them.